Application of different thermal analysis techniques to characterize oxidized olive oils. Issue 1 (14th December 2016) - Vecchio Ciprioti, Stefano; Paciulli, Maria; Chiavaro, Emma
Abstract : The deep changes caused by oxidation on virgin olive oil (VOO), which is a high‐quality product, not subjected to ameliorative refining, make this phenomenon one of the most studied. Among the techniques used to study oxidation in olive oil, thermal analysis (TA) provides useful information about the thermal behavior of the samples as affected by oxidation. Thermogravimetry (TG), measuring the changes in the sample mass, can monitor the kinetics of oil mass loss in decomposition processes or oxidation and has been found particularly useful, especially when operating simultaneously with Differential Thermal Analysis (DTA) or Differential Scanning Calorimetry (DSC). The DSC thermal curves of olive oil, both on cooling and heating, has been found to be largely influenced by the oxidative status of the samples and different statistical approaches have been successfully proposed to correlate the thermal parameters with the conventional chemical indicators of oxidation. DSC can be also used to study the kinetics of phase transition phenomena as affected by oxidation. This review provides an exhaustive survey about the application of the thermoanalytical techniques on this topic proposing them as as a fast and green alternative to conventional chemical methods. Practical applications: The evaluation of the oxidative status of olive oil requires the development of simple and fast analytical techniques. The most used analytical methods are based on the chemical evaluation of the presence of molecules markers of lipid oxidation, but thermal analysis may provide a fast and green tool in this field, as it does not require sample preparation and use of solvents. The application of thermal analysis for the assessment of the oxidative degradation of olive oil has today reached numerous evidences that attest its actual applicability, and they are all summarized in this review. By these studies it is possible to put in evidence its ability to give qualitative information about the oxidative status of olive oil, both in terms of fatty substance degradation and presence of oxidation molecules that could be very helpful in the field of quality assurance for this high‐quality vegetable oil. Thermal analysis as a valuable tool to evaluate olive oil oxidation without sample preparation or use of solvents. Abstract : Thermal analysis as a valuable tool to evaluate olive oil oxidation without sample preparation or use of solvents.